Evaluasi Organoleptik Produk Kristal Jahe Emprit (Zingiber Officinale) di Daerah Istimewa Yogyakarta - Andre Setiawan; Siti Nurlaela; Endah Puspitojati (Food Scientia : Journal of Food Science and Technology, 2022)
Emprit ginger crystal is one of the processed ginger products that is processed through a crystallization. This study aimed to determine the level of differences in consumer preferences for emprit ginger crystal products based on the attributes of taste, aroma, color and texture. This research used a mixed method which was conducted  from February to July 2022. Emprit ginger crystal products (X, Y and Z) were obtained from several ginger processing producers in the Special Region of Yogyakarta (DIY) and the respondents were from the DIY area. The results of data analysis showed that there were significant differences in aroma, color and texture while the taste was not significantly different. The level of consumer preference for product X was in the "rather like" category with an average value of 3.39, product Y in the "like" category with an average value of 4.00 and product Z in the "rather like" category with an average value of 3.47. Evaluation of product X was not sweet, the aroma was right, the color was too dark and the texture was rough. Product Y has the right taste, the right aroma, the brown color tends to be bright and the texture is smooth. Product Z did not have a ginger taste, the aroma was just right, the color was too dark and the texture was smooth.